2004
DOI: 10.1038/sj.leu.2403389
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinone modulates the GM-CSF signaling pathway in TF-1 cells

Abstract: Human leukemogens, including alkylating chemotherapeutic agents and benzene, enhance granulocyte-macrophage colony-stimulating factor (GM-CSF)-dependent proliferation of human CD34 þ bone marrow (BM) cells. The extracellular signal-regulated kinase (ERK) pathway plays an important role in GM-CSF-dependent proliferation and also has been implicated in the pathogenesis of acute myelogenous leukemia. Therefore, we investigated the effects of the benzene metabolite, hydroquinone (HQ), on alterations in the GM-CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(48 reference statements)
1
7
0
2
Order By: Relevance
“…The ChM-I core promoter region contains an AP-1 binding site (Yanagihara et al, 2000), and hydroquinone has been reported to enhance AP-1 activation in TF-1 erythroleukemia cells (Zheng et al, 2004). Whether hydroquinone can up-regulate ChM-I via AP-1 activation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The ChM-I core promoter region contains an AP-1 binding site (Yanagihara et al, 2000), and hydroquinone has been reported to enhance AP-1 activation in TF-1 erythroleukemia cells (Zheng et al, 2004). Whether hydroquinone can up-regulate ChM-I via AP-1 activation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MAP kinases such as ERK, p38 and JNK has been reported Ruiz-Ramos et al, 2005;Zheng et al, 2004a). It has been suggested that 1,4-BQ-induced ROS production leads to the activation of ERK signalling pathway, leading to increased proliferation of leukaemic cells .…”
Section: Supporting Publications 2016: En-955 130mentioning
confidence: 99%
“…Also, HQ can stimulate proliferation and colony formation of human bone marrow progenitor (i.e. CD34+) cells by activation of ERK/AP-1 pathway (Zheng et al, 2004a).…”
Section: Supporting Publications 2016: En-955 130mentioning
confidence: 99%
“…Hydroquinone enhances cytokine-dependent clonal proliferation of a subpopulation of human CD34 + BM cells, which appears to be mediated via the extracellular signal-regulated kinase/activation protein-1 signaling pathway [133][134][135][136]. Hydroquinone has also been reported to synergize with tumor necrosis factor to induce apoptosis in human CD34 + hematopoietic progenitor cells by inhibiting nuclear factorkappa B [137], and to inhibit macrophage-mediated immune responses by modulating intracellular signaling and protective mechanisms [138].…”
Section: Effects Of Benzene Metabolites On the Production Of Chemokinmentioning
confidence: 99%